Peran Kepala Sekolah sebagai Supervisor dalam Meningkatkan Kompetensi Pedagogik Guru di SMP Negeri 3 Doplang - Wulan Fatha Kuri Ain; Muhammad Wildan Shahib (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
Based on the phenomenon that occurred at SMP Negeri 3 Doplang that the implementation of the Teaching and Learning Activities process is less conducive due to several factors including the low motivation of teachers, the use of learning methods that are less varied, and the minimal use of technology that makes the learning atmosphere monotonous due to the lack of available learning tools. This study aims to determine and describe the role of the principal as a supervisor in improving the pedagogical competence of Islamic Religious Education teachers at SMP Negeri 3 Doplang. Researchers used the type of field research with qualitative data. The data collection method used interview, observation and documentation techniques. Data analysis used data reduction techniques, data presentation, data conclusion and verification. The results of the research have been conveyed by the principal of SMP Negeri 3 Doplang that “the role of the principal as supervision is very important, one of which is that the principal always encourages and encourages teachers to take part in various activities, such as seminars, training, workshops, and also courses which will improve the pedagogical competence of the teachers”. Thus, as implementers who are directly involved in the educational process, teachers are at least influenced by encouragement, motivation, supervision and direction from the principal. The research is expected to expand knowledge about the role of school principals as supervisors in improving teachers' pedagogical competence.